Organizational Culture as Predictors of Innovation capability Mediated by Knowledge sharing in Digital creative industry - Maharani, Nanda Dwi; Setia, Shinta (Social Science Studies, 2024)
Research Aims: The progress of the digital creative industry in Indonesia over several decades has had many positive impacts on the Indonesian economy. The creative industry not only makes a major contribution to economic development, but also has a positive impact on the lives of the surrounding community. Currently, many digital creative industries are increasingly carrying out various innovations that are useful for increasing income from business competition in the digital industry. The focus of the inquiry is to offer insight into knowledge sharing (KS) and organizational culture (OC) affect innovation capability (INC) in Indonesia's digital creative sector, especially in the 5 largest cities in Indonesia (Jakarta, Surabaya, Bandung , Makassar, and Medan) Design/methodology/approach: Questionnaires were given to 150 digital creative industry respondents using tools google form, as well as empirical analysis using SEM-PLS and Amos version 22. Research Findings: The results of this watchfulness explain that, according to currently published literature, innovation capability (INC) is profoundly and favorably influenced by organizational culture (OC). then knowledge sharing (KS) can be directly positive influenced by Innovation capability (INC), organizational culture (OC) and Innovation capability (INC) can be indirectly positive influenced by knowledge sharing (KS) activities carried out within a company. Theoretical Contribution/Originality: The focus of the inquiry is to offer insight into knowledge sharing (KS) and organizational culture (OC) affect innovation capability (INC) in Indonesia's digital creative sector, especially in the 5 largest cities in Indonesia (Jakarta, Surabaya, Bandung , Makassar, and Medan)